2018
DOI: 10.3390/neuroglia1010006
|View full text |Cite
|
Sign up to set email alerts
|

l-Dopa and Fluoxetine Upregulate Astroglial 5-HT2B Receptors and Ameliorate Depression in Parkinson’s Disease Mice

Abstract: Here, we report the association between depressive behavior (anhedonia) and astroglial expression of 5-hydroxytryptamine receptor 2B (5-HT2B) in an animal model of Parkinson’s disease, induced by bilateral injection of 6-hydroxydopamine (6-OHDA) into the striatum. Expression of the 5-HT2B receptor at the mRNA and protein level was decreased in the brain tissue of 6-OHDA-treated animals with anhedonia. Expression of the 5-HT2B receptor was corrected by four weeks treatment with either l-3,4-dihydroxyphenylalani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Increasing evidence has suggested that astroglial 5-HT 2B R is involved in depression [96]. In both 1-methyl-4phenyl-1,2,3,6-tetrahydropyridine-induced and 6-hydroxydopamine-induced Parkinson's disease mouse models [97,98], the decrease of astroglial 5-HT 2B R expression paralleled the development of depressive behavior. Treatment with fluoxetine corrected both the decrease of astroglial 5-HT 2B R expression and depressive behavior.…”
Section: Regulation Of Neuroglia Functionmentioning
confidence: 98%
“…Increasing evidence has suggested that astroglial 5-HT 2B R is involved in depression [96]. In both 1-methyl-4phenyl-1,2,3,6-tetrahydropyridine-induced and 6-hydroxydopamine-induced Parkinson's disease mouse models [97,98], the decrease of astroglial 5-HT 2B R expression paralleled the development of depressive behavior. Treatment with fluoxetine corrected both the decrease of astroglial 5-HT 2B R expression and depressive behavior.…”
Section: Regulation Of Neuroglia Functionmentioning
confidence: 98%
“…Reactive astrogliosis represents a complex remodelling of astrocytes, accompanied by changes in gene expression and functional changes; astrogliosis is a genuinely defensive and evolutionarily conserved response, the inhibition of which, as a rule, exacerbates neuropathological development and jeopardises post lesion regeneration (Burda and Sofroniew, 2014). Hence, astrocytes are therapeutic targets for promoting neuroprotection, for example, in stroke and Parkinson’s disease (Song et al, 2018; Vermehren et al, 2018). The astroglial component of neuropathology is highly variable and is often disease specific.…”
Section: Presentmentioning
confidence: 99%